Extract of cassava waste as a lixiviant for gold leaching from electronic waste - Yuranan Photharin; Sirilak Wangngae; Utumporn Ngivprom; Kantapat Chansaenpak; Anyanee Kamkaew; Rung-Yi Lai (Green Chemistry Letters and Reviews, 2022)
Conventional gold leaching from electronic waste requires the use of strong acid and threatens environment. Alternatively, gold can be extracted from electronic waste by the cyanide secreted by bioleaching microorganisms. However, bioleaching microorganisms generally have slow growth rates and require specific growth conditions, restricting their industrial applications. Cassava, a cyanogenic plant containing cyanogenic glucosides, is not currently exploited as a bio-lixiviant source. Cassava is a staple food, and its production is increasing to meet global food requirements. In this work, we developed a protocol to extract cyanide from fresh cassava leaves, an agricultural waste. After multiple extractions, the cyanide concentration reached 120 ppm, higher than the concentration of cyanide produced by cyanogenic microorganisms. Finally, we demonstrated that the extract can be used to leach gold from electronic waste with an efficiency of 69% compared with the control (KCN solution). After optimization of the amount of electronic waste, the recovery reached 26.9%, comparable to that of bioleaching by cyanogenic bacteria. The leaching reaction is selective for gold in the presence of high amounts of Ni and Cu in the electronic waste. The results suggest that cassava leaves are a promising bio-lixiviant source for gold leaching from electronic waste.